2021
DOI: 10.1089/dna.2020.6087
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages as a Double-Edged Weapon: The Use of Macrophages in Cancer Immunotherapy and Understanding the Cross-Talk Between Macrophages and Cancer

Abstract: Macrophages (Mfs) play an essential role in maintaining body homeostasis. They perform dual functions produced by different subtypes. Mfs not only fight against pathogens and foreign bodies such as bacteria or cancer cells but also participate in healing and repairing damaged tissue since they maintain both proinflammatory and anti-inflammatory effects sequentially. Tumors possess the ability to polarize Mfs from proinflammatory M1 subtype to anti-inflammatory M2-like Mfs called tumor-associated macrophages, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 126 publications
(117 reference statements)
1
5
0
Order By: Relevance
“…In addition to impacting the GBM proliferation, our transwell migration data also revealed that MIF1 was able to induce cellular metastasis and invasion of GBM cells when cocultured with M1, M2 or MIF1-induced macrophages. Indeed, these observations clearly fit the model of double function of macrophages, whereby M1 macrophages are responsible for wound healing in the normal context, but those normal functions being responsible for tumor growth and malignancy, and M2 macrophages are responsible for immune responses [44].…”
Section: Discussionsupporting
confidence: 70%
“…In addition to impacting the GBM proliferation, our transwell migration data also revealed that MIF1 was able to induce cellular metastasis and invasion of GBM cells when cocultured with M1, M2 or MIF1-induced macrophages. Indeed, these observations clearly fit the model of double function of macrophages, whereby M1 macrophages are responsible for wound healing in the normal context, but those normal functions being responsible for tumor growth and malignancy, and M2 macrophages are responsible for immune responses [44].…”
Section: Discussionsupporting
confidence: 70%
“…Macrophages were mainly divided into M1 and M2 macrophages. M1 macrophages represented the proinflammatory subtype, activating the immune response, while M2 macrophages constructed an immunosuppressive microenvironment through anti-inflammatory activity [ 42 ]. M1 macrophages as drug carriers accounted for tumor inhibition in gliomas [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypically and functionally similar to M2 macrophages are CD163 and CD206 expressing tumor-associated M2-like macrophages (M2 TAMs) [ 86 ]. TAMs originate from peripheral blood monocytes that infiltrate into the tumor microenvironment in response to cytokines such as VEGF, colony stimulating factor-1 (CSF1), CXC motif chemokine ligand-12 (CXCL12) and various CC motif chemokine ligands (CCL) such as CCL2 [ 87 , 88 ].…”
Section: The Role Of the Immunosuppressive Microenvironment In The Pr...mentioning
confidence: 99%